Randomized, controlled pharmacokinetic and pharmacodynamic evaluation of albinterferon in patients with chronic hepatitis B infection. Issue 1 (January 2015) - Colvin, Richard A; Tanwandee, Tawesak; Piratvisuth, Teerha; Thongsawat, Satawat; Hui, Aric Josun; Zhang, Hongfei; Ren, Hong; Chen, Pei‐Jer; Chuang, Wan‐Long; Sobhonslidsuk, Abhasnee; Li, Ruobing; Qi, Yin; et al.
Abstract Background and Aims Albinterferon is a fusion of albumin and interferon‐α2b developed to improve the pharmacokinetics, convenience, and potential efficacy of interferon‐α for the treatment of chronic hepatitis infections. Methods This open‐label, randomized, active‐controlled, multicenter study investigated the safety and efficacy of albinterferon in patients with chronic hepatitis B virus (HBV) infection who were e‐antigen (HBeAg) positive. One hundred and forty‐one patients received one of four albinterferon doses/regimens or pegylated‐interferon‐α2a. Primary efficacy outcomes were changes in serum HBeAg and antibody, HBV‐DNA, and alanine aminotransferase. Principal safety outcomes were changes in laboratory values, pulmonary function, and adverse events. Results The study was prematurely terminated as phase III trials in hepatitis C infection indicated noninferior efficacy but inferior safety compared with pegylated‐interferon‐α2a. Here, all treatment groups had a significant reduction in HBV‐DNA from baseline. Reductions in HBV‐DNA were not significantly different, except the 1200 μg every 4 weeks albinterferon dose which was inferior compared with pegylated‐interferon‐α2a. The serum alanine aminotransferase levels decreased in all arms. The per‐patient incidence of adverse events was not significantly different for albinterferon (96.4–100%) and pegylated‐interferon‐α2a (93.1%). Total adverse events, however, were higher for albinterferon and correlated to dose. Decreased lung function was found in all arms (∼93% of patients), and was more common in some albinterferon groups. Conclusions Albinterferon doses with similar anti‐HBV efficacy to pegylated‐interferon‐α2a had higher rates of certain adverse events, particularly changes in lung diffusion capacity (http://www.clinicaltrials.gov number NCT00964665).